Social Media Use and High-Risk Sexual Behaviour among Tertiary Institution Students in Kwara State, Nigeria - Ajiboye, Samuel Kolawole (Jurnal Pendidikan Humaniora, 2023)
This study examined the relationship between social media use and high-risk sexual behaviour among tertiary institution students in Kwara State, Nigeria. A total of 561 students were selected by using stratified sampling technique. Data was collected with an instrument titled: Social Media and High-Risk Sexual Behaviour Questionnaire (SMHRSBQ). The measure of central tendency (mean) and mean average were used to determine levels of social media use and involvement in high-risk sexual behaviour. The Pearson’s Product Moment Correlation and One-Way ANOVA Statistics were used to test the null hypotheses at 0.05 alpha level. The Mean Average of responses on social media use was 3.19 while that of high-risk sexual behaviour was 2.83 indicating high levels on both variables among tertiary institution students respectively. Relationship between social media use and high-risk sexual behaviour was significant (p=0.00); no significant difference in social media use and high-risk sexual behaviour based on institution type (University=0.61; Polytechnic=0.13; College of Education=0.06: University=0.11; Polytechnic=0.16; College of Education=0.21) respectively. It was concluded that high use of social media predisposes students to high-risk sexual behaviour. School guidance counsellors should organise seminars periodically to sensitise students on the association between social media use and high-risk sexual behaviour.